DEVELOPMENT OF AN EFFICIENT MECHANISM FOR RAPID PROTOCOLS USING NS-2 SIMULATOR - Abdulwahid, Sarah N. (APTIKOM Journal on Computer Science and Information Technologies, 2018)
The delivered effort in this manuscript is grounded on NS-2 (The Network Simulator 2) to implement thecongestion control process of classic TCP (Transmission Control Protocol), with new congestion control mechanism.In this paper, a novel congestion control algorithm is offered, which contains of slow-start and congestion avoidancemechanisms. The proposed slow-start algorithm assumes a duplicating and an interpolating approach to the congestionwindow (cwnd) for each increment instead of the exponential increment used by other TCP source variants such asReno, Vega, Tahoe, Newreno, Fack, and Sack. Furthermore, the enhanced congestion avoidance algorithm is built byusing an improved Additive Increase Multiplicative Decrease (AIMD) algorithm with multi TCP flow facility, to providean enhanced congestion control algorithm with some valuable properties to improve TCP routine for high speedprotocols. The improvement strategy based on merging of slow start, congestion avoidance mechanism that are usedin TCP congestion control, to create a new AIMD algorithm with a new relationship between the pair parameters aand b. This paper is also involved in the creation of rapid agent in NS-2 models designed to identify the modified TCPand to configure the NS-2 platform. A fast TCP also includes an innovative scheme to slow the rapid start to help TCPto start faster through the high speed networks and also to postpone the congestion state as much as possible.